Dehydrins Impart Protection against Oxidative Stress in Transgenic Tobacco Plants - Halder, Tanmoy; Upadhyaya, Gouranga; Basak, Chandra; Das, Arup; Chakraborty, Chandrima; Ray, Sudipta (Frontiers in Plant Science, 2018)
Environmental stresses generate reactive oxygen species (ROS) which might be detrimental to the plants when produced in an uncontrolled way. However, the plants ameliorate such stresses by synthesizing antioxidants and enzymes responsible for the dismutation of ROS. Additionally, the dehydrins were also able to protect the inactivation of the enzyme lactate dehydrogenase against hydroxyl radicals (OH•) generated during Fenton’s reaction. SbDhn1 and SbDhn2 overexpressing transgenic tobacco plants were able to protect against oxidative damage. Transgenic tobacco lines showed better photosynthetic efficiency along with high chlorophyll content, soluble sugar and proline. However, the MDA content was significantly lower in transgenic lines. Experimental evidence demonstrates the protective effect of dehydrins on electron transport chain in isolated chloroplast upon methyl viologen (MV) treatment. The transgenic tobacco plants showed significantly lower superoxide radical generation (O•−2) upon methyl viologen treatment. The accumulation of the H2O2 was also lower in the transgenic plants. Furthermore, in the transgenic plants the expression of ROS scavenging enzymes was higher compared to non-transformed (NT) or vector transformed (VT) plants. Taken together these data, during oxidative stress dehydrins function by scavenging the (O•−2) directly and also by rendering protection to the enzymes responsible for the dismutation of (O•−2) thereby significantly reducing the amount of hydrogen peroxides formed. Increase in proline content along with other antioxidants might also play a significant role in stress amelioration. Dehydrins thus functions co-operatively with other protective mechanisms under oxidative stress conditions rendering protection in stress environment.